Improving Speaking Skills Through Hand Puppet Media for Class III Students: Peningkatan Keterampilan Berbicara Melalui Media Boneka Tangan Pada Siswa Kelas III - Simanjuntak, Andini Zahara; Rambe, Riris Nurkholidah (Pedagogia : Jurnal Pendidikan, 2025)
This study aims to help students become skilled in speaking in class III of SD IT Al-Hijrah 2 through the implementation of hand puppet media in the learning process. In its implementation, the development method (R&D) through the ADDIE model approach with five stages, namely needs analysis, media design process, development stage, field application, and assessment related to media effectiveness. Linguists, media, and material experts conducted validation, with the average results falling into the “very feasible” feasibility category. The pretest and posttest findings are at a significance value of 0.000, which is below the 0.05 threshold. This indicates that the media trial significantly improved students' speaking ability. Responses from teachers and students also said that this material was interesting and easy to use for education. The research findings show that the use of hand puppet media is not only practical but also successful in fostering an interesting and participatory learning environment and improving students' speaking skills. Highlights: Improves speaking skills significantly using hand puppet media. ADDIE model ensures systematic media development. Validated as highly feasible by education experts. Keywords: Hand Puppet Media, Speaking Skills, Elementary Education, ADDIE Model, Learning Innovation